The Discernment of Ekiti Ethnic Tribe of South Western Nigeria on Wild Edible Vegetables - Joshua Kayode; Modupe Janet Ayeni; Eunice Damilola Akinbinu; Grace Damilola Ogunrotimi (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The discernment of Ekiti people on the wild edible vegetables (WEVs) was conducted in the three senatorial districts of Ekiti State through interviews using a semi-structured questionnaire matrix. The interviews were focused, conversational and two-way in communication. Also the abundance of each of the identified WEVs was determined. The respondents transcend sex, age and literacy status though most of them were females, mostly adults of over 25 years, illiterates, mostly of low economic status and engaged in agricultural activities yet these socio-economic classifications were not pre-requisites to their consciousness on the WEVs. A total of 51 WEVs belonging to 30 families were valued for medicine and nutrition in the study area with the family Asteraceae having the highest number of species. The leaves constituted the major part used in the identified WEVs. The diseases managed and/ prevented by these WEVs were classified into 37 groups while 40 of the WEVs were recognized as sources of vitamins and minerals by the respondents. The need to ensure sustainability of the WEVs in a manner that would improve the dietary and health conditions of the indigenous people of the study area was identified.